Management of child maltreatment suspicions in general practice: a mixed methods study - Camilla Hoffmann Merrild; Hans Christian Kjeldsen; Ioanna Milidou (Taylor & Francis Group, 2023)
AbstractBackground Maltreated children have many long-term consequences throughout their lives, but often maltreated children are not recognised in time by professionals. General practice could be central to the early recognition of child maltreatment due to the long-term relationship with families.Objective How do general practitioners (GPs) and practice nurses (PNs) deal with suspected maltreatment in children below 18 years of age, and which factors influence them to report cases to social authorities.Design and setting A mixed methods study set in general practice in Denmark.Method and subjects We combined data from a nationwide questionnaire with observations from five clinics and 20 interviews with GPs and PNs. We explored our data using the concept of uncertainty as a driver that shapes action and decision-making in general practice.Results Most GPs (94%) said they would discuss cases of suspected child maltreatment with social services, but in many cases they would prefer to discuss their suspicions with a colleague first (83%) - most likely where there are no clear-cut signs. The qualitative data added nuance to these findings by highlighting the difficulty of communicating across sectors, the importance of maintaining a connection with the child's family, and practicing watchful waiting.Conclusion General practice has an opportunity to act early in cases of suspected child maltreatment if uncertainty is accepted as a critical part of the process of reaching a diagnosis. Communication across sectors is key, as is support for GPs with suspicions and for families in need of help.Key pointsGPs are often thought to underreport child maltreatment but despite low levels of reporting, this does not mean they ignore it.Building on the connection with the family, making follow appointments, and discussing suspicions with colleagues are typical of how GPs manage suspicions of child abuse.Accepting uncertainty as a condition of raising the alarm could help GPs to act quickly to support children at risk of abuse.